PlayAnywhere: A Compact Interactive Tabletop Projection-Vision System - Wilson, Andy (UIST '05 Proceedings of the 18th annual ACM symposium on User interface software and technology, 2005)
We introduce PlayAnywhere, a front-projected computer vision-based interactive table system which uses a new commercially available projection technology to obtain a compact, self-contained form factor. PlayAnywhere’s configuration addresses installation, calibration, and portability issues that are typical of most vision-based table systems, and thereby is particularly motivated in consumer applications. PlayAnywhere also makes a number of contributions related to image processing techniques for front-projected vision-based table systems, including a shadow-based touch detection algorithm, a fast, simple visual bar code scheme tailored to projection-vision table systems, the ability to continuously track sheets of paper, and an optical flow-based algorithm for the manipulation of onscreen objects that does not rely on fragile tracking algorithms.